Association between snacking and obesity in children: a review - Nuru, Hasanuddin; Mamang, Fardiana (International Journal Of Community Medicine And Public Health, 2017)
Snacking is consumption of food and drinks between meals, which has contradict perception toward intake quality of the children. This study aim to inform the readers how snacking associated with weigh gain in the children. This data was collected from published papers between January 2004 to 2014 used Google scholar and PubMed databases. The articles were limited to English language only which focus on snacking, obesity and children as keywords. Snacking has great influence to the diet quality of the children particularly body mass index (BMI). Those who ate snack with large portion and size more frequently will have high risk to be obesity conversely those who eat snack without hungry feel will improve diet quality in children. Snacking is not only independent factor that contribute to the weight gain in children but it also has positive impact to the diet quality. Further investigation needed to find the clear understanding of influence or association of snacking toward weight gain.